Exploring the Impact of Auditor Burnout on Job Performance: The Roles of Depersonalisation and Reduced Personal Accomplishment in Jayapura, Papua - Putri Ratnasari; Elia Madatu Tandililing; Ulfah Rizky Muslimin (Manunggal Halim Jaya, 2026)
Audit quality plays a critical role in maintaining the credibility of financial statements; however, excessive work pressure may trigger auditor burnout and potentially reduce audit performance quality. This issue is important to examine because burnout affects not only individual auditors but also organisational sustainability and public trust. This study aims to analyse the influence of three burnout dimensions, namely emotional exhaustion, depersonalisation, and reduced personal accomplishment, on job satisfaction, job performance, and turnover intention among auditors. This study adopts a quantitative explanatory design using a cross-sectional survey approach. The research population consists of auditors working in government agencies, state-owned enterprises, and public accounting firms in Jayapura, Papua. A purposive sampling technique was employed, resulting in 100 auditors who met the criterion of having at least one year of audit experience. Data were collected using a structured questionnaire with a four-point Likert scale and analysed using canonical correlation analysis to examine the simultaneous relationship between burnout dimensions and work outcomes. The results indicate that emotional exhaustion does not have a significant relationship with job satisfaction, job performance, or turnover intention. In contrast, depersonalisation shows a significant relationship with job performance and turnover intention, while reduced personal accomplishment is significantly related to job performance but not to job satisfaction or turnover intention. Overall, depersonalisation emerges as the most influential burnout dimension affecting auditors’ work outcomes. The findings highlight the importance of organisational policies aimed at reducing depersonalisation through social support mechanisms, fostering a collaborative work environment, and strengthening recognition systems and competency development programmes to enhance auditors’ sense of personal accomplishment and performance.